Accounting for linkage between the STR loci D5S818/CSF1PO and vWA/D12S391 in kinship analyses: Impact on likelihood ratio values. (December 2015) - Burri, H.; Sulzer, A.; Voegeli, P.; Kratzer, A.
Abstract: For kinship testing, it is important to consider the issue of genetic linkage when evaluating data from closely positioned short tandem repeat (STR) loci. The aim of our study was to assess the impact of ignoring vs. accounting for linkage on likelihood ratio (LR) values in kinship analyses. We took linkage into account by incorporating the recombination frequency into LR calculations and studied the effect of linkage between D5S818 and CSF1PO in the pedigree scenario "full siblings vs. unrelated" for 65 pairs of full siblings and 65 pairs of unrelated persons. For the marker pair vWA and D12S391, we evaluated 46 cases of kinship testing from our institute and compared the approach of incorporating the recombination frequency into LR calculations with the alternative option of dealing with linkage by including only one of two closely positioned loci in a kinship analysis.